Sustainable alternatives for poverty. reduction and eco-justice - Andrianos, Lucas (Cambridge Scholars Publishing, 2014)
This book presents edited and revised versions of most of the papers presented at the First International Conference on Sustainable Alternatives for Poverty Reduction and Ecological Justice in 2012 (SAPREJ-12). The selected papers are classified into six thematic sections: Biodiversity and ecological crisis; Sustainability, religion and ethics; Climate change, eco-justice and health; Poverty, financial crisis and human rights; Green economy and food security; and Global crisis and case studie ...